2003
DOI: 10.1242/dev.00527
|View full text |Cite
|
Sign up to set email alerts
|

Splits ends is a tissue/promoter specific regulator of Wingless signaling

Abstract: Wingless directs many developmental processes inDrosophila by regulating expression of specific target genes through a conserved signaling pathway. Although many nuclear factors have been implicated in mediating Wingless-induced transcription, the mechanism of how Wingless regulates different targets in different tissues remains poorly understood. We report here that the split ends gene is required for Wingless signaling in the eye, wing and leg imaginal discs. Expression of a dominant-negative version of spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 70 publications
0
41
0
Order By: Relevance
“…Because the large SPOC family member spen is required for Drosophila eye development (Dickson et al 1996;Rebay et al 2000;Lin et al 2003) and the fly eye provides a uniquely powerful system in which to explore functional relationships between signaling molecules (Zipursky and Rubin 1994), we focused our analyses on this tissue. RT-PCR confirmed that nito, like spen, is expressed in the developing eye disc (Figure 4 and data not shown), further validating the approach.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the large SPOC family member spen is required for Drosophila eye development (Dickson et al 1996;Rebay et al 2000;Lin et al 2003) and the fly eye provides a uniquely powerful system in which to explore functional relationships between signaling molecules (Zipursky and Rubin 1994), we focused our analyses on this tissue. RT-PCR confirmed that nito, like spen, is expressed in the developing eye disc (Figure 4 and data not shown), further validating the approach.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated the consequences of increasing or decreasing nito levels in the background of a dominant negative spen transgene (spen DN ), which encodes the C-terminal 936 amino acids of spen (Lin et al 2003) and also produces dose-sensitive phenotypes (D. Doroquez and I. Rebay, unpublished results). Because both transgenes are capable of perturbing eye development on their own, to distinguish between additive and synergistic interactions we used a NITO-FL transgenic line that when expressed with sev weak exhibits only very mild perturbations of the adult eye ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies found that spen is implicated in a variety of cellular and developmental processes including neuronal cell fate specification, axon guidance, cell cycle, Hox gene regulation, and cell death (27)(28)(29)(30). These pleiotropic effects are likely due to the involvement of spen in multiple signaling pathways (31)(32)(33). However, the molecular mechanisms underlying the function of Spen in these pathways are not understood.…”
Section: Discussionmentioning
confidence: 99%